(untitled) (Eurasian Medical Research Periodical, 2022)
The great social significance of diseases of the ear, throat and nose is determined by their high incidence in childhood. The prevalence of chronic otorhinolaryngological pathology in children in Uzbekistan ranges from 181.9 to 465.0 per 1000 of the child population, while adenotonsillar pathology occupies a leading position